Evolutionary information dynamics over social networks: a review - Hangjing Zhang; Yan Chen; H. Vicky Zhao (International Journal of Crowd Science, 2020)
PurposeThe purpose of this paper is to have a review on the analysis of information diffusion based on evolutionary game theory. People now get used to interact over social networks, and one of the most important functions of social networks is information sharing. Understanding the mechanisms of the information diffusion over social networks is critical to various applications including online advertisement and rumor control.Design/methodology/approachIt has been shown that the graphical evolutionary game theory (EGT) is a very efficient method to study this problem.FindingsBy applying EGT to information diffusion, the authors could predict every small change in the process, get the detailed dynamics and finally foretell the stable states.Originality/valueIn this paper, the authors provide a general review on the evolutionary game-theoretic framework for information diffusion over social network by summarizing the results and conclusions of works using graphical EGT.